Coping Mechanisms of Microenterprises during the COVID-19 Pandemic in Baybay City, Leyte - Lorrelyn Calvo; Ana Liza M. Recto; Charmagne Faith F. Capuno; Babylyn C. Lambert; Ian Dave B. Custodio (Review of Socio-Economic Research and Development Studies, 2023)
This study examines the different coping mechanisms adopted by microenterprises to mitigate the effect of the pandemic in Baybay City, Leyte. Using a structured survey questionnaire, a total of 138 microentrepreneurs from 12 villages or barangays in Baybay, City were interviewed. The data revealed that most of these microentrepreneurs were engaged in small retail businesses. During the pandemic, they experienced a significant reduction in their sales and incurred higher transportation costs. Most of these businesses do not have another source of income. Unfortunately, others have temporarily closed their business. Results show that most micro-entrepreneurs in Baybay have one to two coping strategies in response to disruption brought by the pandemic. Some of these strategies include selling new products such as face masks and using their other sources of income to buy necessities for their home and business. The descriptive analysis showed that female-owned microenterprises have explored more coping mechanisms than male-owned microenterprises. The regression results show that having a secondary source of income influences the capacity of microentrepreneurs to explore more coping strategies as compared to others with only one source of income. In addition, a large proportion of microentrepreneurs did not attend business-related training. Hence, it is recommended that microentrepreneurs may consider attending trainings, including risk management workshops. Microentrepreneurs also need more access to financial support and subsidies to cope with the disruption. Results of the study highlighted the importance of livelihood diversification to help manage the risk of losing a business during the pandemic. The results from this research may be used as a baseline information to provide insights for the government in crafting policies concerning managing risk during the pandemic.